Pengaruh Kualitas Produk dan Kualitas Pelayanan terhadap Kepuasan Pelanggan - Puspitasari, Devi; Nurmaning, Bina Andri (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2024)
This study aims to determine the effect of product quality, service quality on customer satisfaction. This type of research uses quantitative research. The population in this study were customers of Kedai Coffee ACC Tulungagung. The sample in this study was 100 respondents with the accidental sampling technique. Data collection techniques used questionnaires and observations. Data analysis techniques used multiple linear regression analysis with SPSS version 27. Hypothesis testing used the t test, F test and determination coefficient test (R2). The results of this research are: 1) Product quality has a positive and significant effect on customer satisfaction, 2) Service quality has a positive and significant effect on customer satisfaction, 3) product quality and service quality have a positive and significant effect on customer satisfaction.